Realization of quantum permutation algorithm in high dimensional Hilbert space - 陈东旭 刘瑞丰 张沛 王云龙 李宏荣 高宏 李福利 (Chinese physics B, 2017)
Quantum algorithms provide a more efficient way to solve computational tasks than classical algorithms. We experimentally realize quantum permutation algorithm using light＇s orbital angular momentum degree of freedom. By exploiting the spatial mode of photons, our scheme provides a more elegant way to understand the principle of quantum permutation algorithm and shows that the high dimension characteristic of light＇s orbital angular momentum may be useful in quantum algorithms. Our scheme can be extended to higher dimension by introducing more spatial modes and it paves the way to trace the source of quantum speedup.